Advertorial Online: Jembatan Komunikasi antara Lembaga Amil Zakat dan Masyarakat - Imran, Maharani (Institut Ilmu Sosial dan Manajemen Stiami, 2025)
Online advertorials have become an effective communication medium for conveying information and building relationships between Amil Zakat Institutions and the community. This community service program aims to implement the creation of an online advertorial as a communication bridge between the Amil Zakat Institution and the community. Implementing this community service activity involves college students developing relevant and interesting advertorial content. College students help Panti Yatim Indonesia (PYI), which has never used online advertorials, to use this media optimistically. This program shows that online advertorials can increase awareness, trust, and community participation in supporting PYI programs. This article ends with strategic suggestions for optimizing online advertorials as a communication medium for Amil Zakat institutions.